(untitled) - Patrick R Delaney (New York, 1998)
The book provides study outlines of Financial Accounting and Reporting: Business Enterprises. It includes a detailed solution guide for each accounting problem and outlines of the unofficial answers to essay questions published by the AICPA
Keywords: managerial accounting,managerial economic